High yield production of Rhizobium NodB chitin deacetylase and its use for in vitro synthesis of lipo-chitinoligosaccharide precursors - Chambon, Rémi (Carbohydr Res, 2017)
Lipo-chitinoligosaccharides (LCOs) are key molecules for the establishment of plant-microorganisms symbiosis. Interactions of leguminous crops with nitrogen-fixing rhizobial bacteria involve Nod factors, while Myc-LCOs improve the association of most plants with arbuscular mycorrhizal fungi. Both Nod factors and Myc-LCOs are composed of a chitinoligosaccharide fatty acylated at the non-reducing end accompanied with various substituting groups. One straightforward way to access LCOs is starting from chitin hydrolysate, an abundant polysaccharide found in crustacean shells, followed by regioselective enzymatic cleavage of an acetyl group from the non-reducing end of chitin tetra- or pentaose, and subsequent chemical introduction of N-acyl group. In the present work, we describe the in vitro synthesis of LCO precursors on preparative scale. To this end, Sinorhizobium meliloti chitin deacetylase NodB was produced in high yield in E. coli as a thioredoxin fusion protein. The recombinant enzyme was expressed in soluble and catalytically active form and used as an efficient biocatalyst for N-deacetylation of chitin tetra- and pentaose.